Domestic violence against children - Mihić Biljana D. (Temida)
In this paper the author is analysing definitions and basic notions related to domestic violence against children, as one of the most serious forms of violence. The special chapter deals with effects of violence against children and causes of domestic violence against them. Also, the author is analysing different forms of social reaction and considering the problem of legal regulation of mandatory reporting domestic violence against children.